2014
DOI: 10.1080/03670244.2013.774674
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Two Indices of Diet Quality with Acculturation Factors and Demographics in Haitian Americans

Abstract: This study examined associations of language preference and length of stay in the United States and diet among 132 Haitian Americans aged ≥35, born in Haiti. Two dietary indices, Healthy Eating Index (HEI) and Alternative Healthy Eating Index (AHEI), were used to assess dietary quality. Years in the United States (>15 years; B = 0.063, p = .012) and female gender (B = 5.63, p = .028) were positively associated with AHEI. Lower HEI scores were associated with speaking no English (B = -6.11, p = .026). Participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…A diet quality index measures most important dietary components and scores depending on these components. The assessment of adequacy, diversity and proportionality of diet is carried with diet quality indices [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A diet quality index measures most important dietary components and scores depending on these components. The assessment of adequacy, diversity and proportionality of diet is carried with diet quality indices [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is updated at every five years [ 22 , 24 , 27 ]. HEI score was found to be negatively associated with diseases such as abdominal obesity, hypertension, cancer in many studies [ 22 , 23 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…More recent studies conducted among other Hispanic populations, including Puerto Rican and Dominican subgroups, show consistent findings ( Kershaw et al, 2016 , Lin et al, 2003 , Pérez-Escamilla and Putnik, 2007 ). Two known studies conducted among non-Hispanic Caribbean immigrants show mixed findings ( Allen et al, 2014a , Ayala et al, 2008 , Huffman et al, 2014 ). One study showed an association between lower acculturation and poor diet quality/less healthful intakes, while the other found that more acculturated persons had poorer dietary quality ( Allen et al, 2014b , Huffman et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Two known studies conducted among non-Hispanic Caribbean immigrants show mixed findings ( Allen et al, 2014a , Ayala et al, 2008 , Huffman et al, 2014 ). One study showed an association between lower acculturation and poor diet quality/less healthful intakes, while the other found that more acculturated persons had poorer dietary quality ( Allen et al, 2014b , Huffman et al, 2014 ). The mixed findings likely reflect differences in quality and type of food intakes attributed to diverse regions or urbanicity within in the country of origin and varied measurement of acculturation.…”
Section: Introductionmentioning
confidence: 99%
“…The gender, age and risk factor associations found in this study are consistent with prior work, further demonstrating the utility of Nutri-eSCREEN®. For example, prior work has found associations between poorer diet quality and inadequate dentition, increasing age, male gender, and fewer meals per day [32][33][34][35]. Persons at risk for chronic conditions such as those with pre-diabetes [29] could be key targets for Nutri-eSCREEN®.…”
Section: Discussionmentioning
confidence: 99%